Robotics in neurosurgery: the past, present and the future - Sagun Ghimire; Shikher Shrestha; Dinuj Shrestha; Sudarshan Awal (Egyptian Journal of Neurosurgery)
Abstract With the global advancement in robotics, the field of neurosurgery has also progressed futuristically. There are several subspecialties ranging from skull based and cranial surgeries to spinal surgeries along with stereotactic and functional surgery, neuroendovascular, neurointerventional surgery where robotics have dramatically impacted the patient care. Combining the fluency, accuracy, flexibility and dynamics of robotics with operating neurosurgeons innate surgical skill sets, it has marched the arena of robotic neurosurgery way forward beyond the realms of traditional surgical modalities such as open to laparoscopic surgeries. Despite the global race in technical advancement in terms of robotic surgery, there still exists a basic robotics surgery training curriculum so as to train the upcoming neurosurgeon trainees. There still exists a global demand for standardized training protocol and fellowship programs for full-fledged training of neurosurgery residents all over the world, even for the trainees from lower middle-income countries. The frontrunners from global neurosurgical community have focused more on just development of such modalities, but their balanced dissemination globally should also be propagated. With technological development, the matter of ethical and moral segments should also be introspected so as to allow robotics to work more smoothly with less prospects of potential ethical litigations. Hence, there is also a need for revision of ethical guidelines so as to guide any robotics surgeon of any specialty to work fluently. Moreover, globally there exists very small group of nations, mostly the USA and European countries, and some of the Asian countries, such as Japan, China, Korea and India, house such robotic advancement in neurosurgery; hence, there exists a major demand to disseminate the ideas and technology globally. In the coming future, the prospect of artificial intelligence and virtual reality-guided robotics neurosurgery is also on uprise, which when combined with robotic dynamics can bring about a significant paradigm shift in the field of neurosurgery.